2009
DOI: 10.1098/rspb.2008.1748
|View full text |Cite
|
Sign up to set email alerts
|

Predator crypsis enhances behaviourally mediated indirect effects on plants by altering bumblebee foraging preferences

Abstract: Predators of pollinators can influence pollination services and plant fitness via both consumptive (reducing pollinator density) and non-consumptive (altering pollinator behaviour) effects. However, a better knowledge of the mechanisms underlying behaviourally mediated indirect effects of predators is necessary to properly understand their role in community dynamics. We used the tripartite relationship between bumblebees, predatory crab spiders and flowers to ask whether behaviourally mediated effects are loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 33 publications
1
49
0
4
Order By: Relevance
“…Previously it has been shown that bees responded to variation in task difficulty or task risk by slowing down to improve accuracy (18,26), and in an ethological setting bees responded to a cryptic predation risk by shifting their foraging strategy, perhaps akin to opting out of difficult discriminations in our assay (27). These findings raise the question of how bees are doing this.…”
Section: Discussionmentioning
confidence: 50%
“…Previously it has been shown that bees responded to variation in task difficulty or task risk by slowing down to improve accuracy (18,26), and in an ethological setting bees responded to a cryptic predation risk by shifting their foraging strategy, perhaps akin to opting out of difficult discriminations in our assay (27). These findings raise the question of how bees are doing this.…”
Section: Discussionmentioning
confidence: 50%
“…Their behavioral responses to these disturbances were then measured. For instance, free-flying bees foraging for sucrose solution learned to avoid flower patches infested with real or robotic crab spiders (Dukas, 2001;Dukas and Morse, 2003;Ings and Chittka, 2008;Ings and Chittka, 2009), or artificial flowers when penalized either with quinine (Chittka et al, 2003;Avarguès-Weber et al, 2010) or a puff of compressed air (Gould, 1986). Aversive treatments given in a context in which a sucrose reward is also delivered induce an increase in choice accuracy in difficult perceptual discriminations (Chittka et al, 2003;Ings and Chittka, 2008;Avarguès-Weber et al, 2010).…”
Section: Prior Studies On Honeybee Punishment Learningmentioning
confidence: 99%
“…In particular, a single predator species may simultaneously suppress both herbivores and pollinators. For example, crab spiders can capture various flower visiting insects, including flower herbivores such as beetles and moths, as well as pollinators such as honeybees and even bumblebees (Dukas & Morse 2003;Suttle 2003;Dukas 2005;Robertson & Maguire 2005;Ings & Chittka 2009), and many birds and reptiles known as predators of phytophagous insects also consume insect pollinators (Suttle 2003;Muñoz & Arroyo 2004;Meehan et al 2005). These examples imply that a single generalist predator species may have contrasting effects on plant fitness (Romero & Koricheva 2011).…”
Section: Introductionmentioning
confidence: 99%